2008
DOI: 10.1021/bi702252d
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding Specificity ofDrosophilaMuscleblind

Abstract: Members of the muscleblind family of RNA binding proteins found in Drosophila and mammals are key players in both the human disease myotonic dystrophy and the regulation of alternative splicing. Recently, the mammalian muscleblind-like protein, MBNL1, has been shown to have interesting RNA binding properties with both endogenous and disease-related RNA targets. Here we report the characterization of RNA binding properties of the Drosophila muscleblind protein Mbl. Mutagenesis of double-stranded CUG repeats dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…This is particularly conspicuous in the most highly conserved block of 40 nucleotides in the DSE120. Such a sequence pattern bears the hallmarks of the optimal binding site for the CELF and MBNL (Muscleblind-like) families of splicing regulatory proteins (9,12). To investigate whether any CELF or MBNL proteins function as regulators of LEF1 splicing, we first used a UV cross-linking assay to determine in an unbiased fashion what proteins bind to the LEF1 regulatory sequences.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly conspicuous in the most highly conserved block of 40 nucleotides in the DSE120. Such a sequence pattern bears the hallmarks of the optimal binding site for the CELF and MBNL (Muscleblind-like) families of splicing regulatory proteins (9,12). To investigate whether any CELF or MBNL proteins function as regulators of LEF1 splicing, we first used a UV cross-linking assay to determine in an unbiased fashion what proteins bind to the LEF1 regulatory sequences.…”
Section: Resultsmentioning
confidence: 99%
“…An AC-rich motif matching hnRNP L binding sites was the third most significant repressive motif, and hnRNP L has been reported to play a role in regulating translation of some mRNAs (Ray et al 2009). Two 8-mers containing one or two occurrences of UGCU, the canonical binding motif of MBNL proteins (Goers et al 2008), occurred lower down on the list, albeit with Q-values of 0.4 and 0.7. MBNL proteins regulate pre-mRNA splicing, but are also expressed cytoplasmically and have been implicated in control of mRNA localization and translation (Wang et al 2012).…”
Section: Motifs Associated With Translational Repressionmentioning
confidence: 99%
“…Muscleblind proteins from different species can also regulate the splicing of ortholog transcripts. Drosophila melanogaster Muscleblind binds to human cardiac troponin T ( cTNT ) pre‐mRNAs (Goers et al , 2008) and is able to regulate mouse fast skeletal muscle Troponin T ( TnnT3 ) splicing (Vicente‐Crespo et al , 2008). This indicates that Muscleblind targets are strongly conserved through evolution.…”
Section: Alternative Splicing Regulation By Muscleblind Proteinsmentioning
confidence: 99%
“…These motifs bind to RNA molecules in a sequence‐specific fashion (Worthington et al , 1996). Different studies have demonstrated that both human and Drosophila melanogaster Muscleblind zinc fingers recognize RNA hairpins containing mismatched pyrimidines (Goers et al , 2008; Warf & Berglund, 2007; Yuan et al , 2007). Moreover Drosophila melanogaster Muscleblind zinc fingers specifically bind a human MBNL1 RNA target indicating that recognition mechanisms of pre‐mRNA targets by Muscleblind zinc finger domains are conserved (Goers et al , 2008).…”
Section: Alternative Splicing Regulation By Muscleblind Proteinsmentioning
confidence: 99%